Death gone a-rye - Archer, Winnie (Archer, Winnie. Bread shop mystery., 2021)
"Vincent van Dough focaccia is being touted on Instagram as the best thing since sliced bread...But one person won't be tasting the Mexican bakery's latest specialty. Ambitious school board president Nessa Renchrik has been murdered. Like the rest of this close-knit community, Ivy is shocked. But she's just as surprised to discover her beau-restaurateur Miguel Baptista-had his own fling with Nessa back in the day and now the police have this half-baked notion he might have killed her"--